2014
DOI: 10.3389/fncel.2014.00227
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic outcomes of transplantation of amniotic fluid-derived stem cells in experimental ischemic stroke

Abstract: Accumulating preclinical evidence suggests the use of amnion as a source of stem cells for investigations of basic science concepts related to developmental cell biology, but also for stem cells’ therapeutic applications in treating human disorders. We previously reported isolation of viable rat amniotic fluid-derived stem (AFS) cells. Subsequently, we recently reported the therapeutic benefits of intravenous transplantation of AFS cells in a rodent model of ischemic stroke. Parallel lines of investigations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…Other molecular pathways for axonal sprouting, either induced in peri-infarct neurons or contralateral neurons [98], indicate promising targets for neural repair such as ephrin-A5, GDF10, and the use of the small molecule inosine [36,69,98,113]. Cell therapies appear to stimulate local axonal sprouting by tissue immunohistochemical staining [117][118][119], and in some cases by more detailed direct demonstration of axonal connections [120]. These also represent a candidate neural repair approach.…”
Section: Potential Neural Repair Therapiesmentioning
confidence: 99%
“…Other molecular pathways for axonal sprouting, either induced in peri-infarct neurons or contralateral neurons [98], indicate promising targets for neural repair such as ephrin-A5, GDF10, and the use of the small molecule inosine [36,69,98,113]. Cell therapies appear to stimulate local axonal sprouting by tissue immunohistochemical staining [117][118][119], and in some cases by more detailed direct demonstration of axonal connections [120]. These also represent a candidate neural repair approach.…”
Section: Potential Neural Repair Therapiesmentioning
confidence: 99%
“…Acosta and colleagues have provided preclinical evidence of safety and efficacy of stem cell therapy in traumatic brain injury [26,27] and in stroke [28,29]. In this article, they highlight the bioethical issues that have accompanied this cell therapy over the last two decades and raised public concern, including safety measures, commercialization, and confidentiality of donors.…”
Section: Bridging the Gap Between The Public And Scientific Communitymentioning
confidence: 99%
“…been used to treat stroke in rat models, and it was found that both motor and cognitive deficits were reduced after the transplantation. Furthermore, the cell proliferation in the subventrical zone (SVZ) was increased (Tajiri et al, 2014). However, amniotic fluid-derive cells are a heterogeneous cells population with diverse phenotypes.…”
Section: Instructionmentioning
confidence: 99%